en - Bere, Stefanus Dendy Prasetya; Pratiwi, Desak Putu Eka (e-Journal of Linguistics; Vol 16 No 1 (2022): ejl-JanuaryDO - 10.24843/e-jl.2022.v16.i01.p12, 2021)
This article entitled "Exposing the Meaning of Figurative Language in Alie Gatie Selected song lyrics". Figurative language is sentences or phrases that possess secret meanings behind the word, phrases, or sentences. This article aims to exposing the types of figurative language and uncover the meaning of figurative language used in Alie Gatie selected song lyrics. The writer is interested in analyzing Alie Gatie selected songs since Gatie’s songs are telling stories of his love stories and his heartbreak. The datas were obtained by the method of observating and taking notes. The obtained data were then analyzed by descriptive qualitative method using theory proposed by Knickerbocker and Reninger (1963) to identify the types of figurative language and theory of meaning by Leech (1981) to expose the meaning of figurative language. The finding shows that there are various figurative languages used in Alie Gatie’s selected songs such as Metaphor, Irony, Hyperbole, and Paradox.